A Distributed Pseudonym Management Scheme in VANETs. (30th April 2013) - Zhu, Xiaoling; Lu, Yang; Zhang, Benhong; Hou, Zhengfeng
Security and privacy have been important issues in VANETs. Anonymity is an effective way to achieve privacy protection, and it sometimes requires to be disclosed for determining traffic liability. In most pseudonym schemes, an authority is aware of a vehicle's secret, and its compromise will result in the leakage of a large amount of privacy information. So, we propose a distributed traceable pseudonym management scheme in VANETs. In the scheme, a blind signature method is adopted to achieve strict separation of issuance and tracking. The distributed tracking protocol is proposed to enhance the robustness for tracking, which is based on the improved scheme for shared generation of RSA keys. An efficient pseudonymous authentication mechanism is proposed to reduce the communication overhead. Compared with other related proposals, our scheme is unforgeability, especially against authority forge attacks, and has better robustness. Moreover, the performance analysis shows that it is efficient in VANETs.